The Frazier site: an agate basin occupation and lithic assemblage on the Kersey Terrace, northeastern Colorado - Slessman, Scott A., author; Todd, Lawrence C., 1954-, advisor; Zier, Christian J., committee member; Hill, Matthew G. (Matthew Glenn), committee member; Eighmy, Jeffrey L., committee member; Kelly, Eugene Francis, committee member (Colorado State University. Libraries, 2004)
The Frazier site was discovered by Frank Frazier in 1965, and was excavated from 1965 to 1967 by the Denver Museum of Natural History under the direction of H. Marie Wormington. An analysis of the lithic assemblage and a description of the excavations are provided in this thesis because this information has never been published in any detail. The Frazier site is an Agate Basin bison kill-butchery site located near the town of Kersey, Colorado. The Frazier site is important not only because it is one of a few Agate Basin sites on the Northwest Plains, but also because it was the last major excavation directed by H. Marie Wormington for the Denver Museum of Natural History. The Frazier collection is comprised of 1,161 lithic artifacts and 20,012 pieces of bone. Interpretations of Agate Basin activities at the Frazier site are based on the analysis of the lithic material (debitage and tools), and the raw material composition of the collection. In addition to a traditional lithic analysis, the Frazier collection is inspected through the use of minimum nodule analysis (MNA). An examination of the spatial distribution of cultural remains indicates that several distinct activity areas are located at the site. The results of the analysis are used to compare the Frazier data with other Paleoindian sites in the region, particularly with Agate Basin period sites. Unlike the other long-term, multiple-event Agate Basin localities (Agate Basin site, Hell Gap site), the results of the analysis indicate that the Frazier site represents a single-event, short-term bison kill-butchery and processing occupation. The Frazier site therefore offers a different view of Agate Basin behavior on the Plains. Aspects of Agate Basin lithic technology, subsistence, site structure and function, and mobility at a kill/processing site are discussed.
Keywords: Colorado -- Antiquities; Stone implements -- Colorado -- Frazier Site